1993
DOI: 10.1128/jvi.67.2.716-725.1993
|View full text |Cite
|
Sign up to set email alerts
|

Papillomavirus E7 protein binding to the retinoblastoma protein is not required for viral induction of warts

Abstract: Human papillomaviruses (HPVs) are the etiologic agents responsible for benign epithelial proliferative disorders including genital warts and are a contributory factor in the pathogenesis of cervical cancer. HPVs demonstrate strict species and cell-type specificity, which is manifested by the inability of these viruses to induce disease in any species other than humans. The natural history of HPV infection in humans is closely mimicked by cottontail rabbit papillomavirus (CRPV) infection in domestic laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 75 publications
1
26
0
Order By: Relevance
“…able to bind IGFBP-3 and trigger its degradation. This finding suggests that the interaction of E7 with the retinoblastoma family of proteins is not required for inactivation of IGFBP-3 and strengthens the notion that several distinct regulatory pathways must be subverted by E7 in order to transform mammalian cells, in keeping with the results from numerous genetic (7,8,17,20,25,41,84) and biochemical (4,5,14,19,24,28,42,54,65,79,89,93,94) studies (for a recent review, see reference 91).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…able to bind IGFBP-3 and trigger its degradation. This finding suggests that the interaction of E7 with the retinoblastoma family of proteins is not required for inactivation of IGFBP-3 and strengthens the notion that several distinct regulatory pathways must be subverted by E7 in order to transform mammalian cells, in keeping with the results from numerous genetic (7,8,17,20,25,41,84) and biochemical (4,5,14,19,24,28,42,54,65,79,89,93,94) studies (for a recent review, see reference 91).…”
Section: Discussionsupporting
confidence: 63%
“…Cell lysates were prepared and subjected to immunoprecipitation with antibodies to E7 and IGFBP-3 and control antibodies, as indicated. Precipitated proteins were detected by Western blotting.VOL 20,. 2000 HPV-16 E7 BINDS AND INACTIVATES IGF-BINDING PROTEIN also drastically reduced in the supernatants of E7-expressing cells.…”
mentioning
confidence: 99%
“…Analogous data were obtained using the cottontail rabbit papillomavirus (CRPV) model. In these studies mutants of CRPV E7, which were not able to bind Rbl , were still able to induce wart formation in rabbits (29). The data obtained suggest that the interaction of Rbl is not important in the early state of the infection cycle.…”
Section: E7/rb 1 Interaction and Cellular Transformationmentioning
confidence: 80%
“…Whereas binding of the Rb protein family by E7 is mediated by conserved domain 2 of the viral protein, it was shown that functional inactivation of pRb also requires sequences in the very N-terminal and the C-terminal part of E7, in addition to the pRbbinding interface (17,25). The C-terminal half of the E7 protein is essential for immortalization and transformation of human cells (26,27). Whereas the mechanisms by which the C-terminal domain of E7 contributes to cell transformation are not entirely clear, numerous cellular regulatory proteins have been identified, which are bound by E7 via its C-terminal part.…”
mentioning
confidence: 99%